Capacity of Surface Production of Band Sawing in Manufacture of Oak Floor Upper Layers - Orlowskl, Kazimierz A.; Chuchala, Daniel; Stenka, Dawid; Przybylinski, Tomasz (BioResources, 2023)
Thin lamellae, corresponding to the layer components of structural glued members, i.e., 2-ply or 3-ply glued flooring, can be manufactured in re-sawing operations of kiln-dried wood blocks or in wet technologies, which currently seem to be more common because of the shorter drying time. The re-sawing process in wet technology is conducted on dedicated thin-cutting band sawing machines with stellite-tipped band saws. The goal of this research was to demonstrate the capacity of surface production (m2/ tool life) of visible layers of oak engineered flooring composites in a function of both a new band saw and a re-sharpened band saw blade. Additionally, the state of teeth of each band saw blade was examined at the end of the tool life. A series of cutting tests were performed in sawmill production conditions. The conducted tests revealed that a three times higher capacity of surface production was obtained for the new tool compared to re-sharpened tool. Additional microscopic observations of some re-sharpened teeth showed deformed plastic characteristics.